Improving EFL Learners' Writing Accuracy and Fluency through Task-based Collaborative Output Activities and Scaffolding Techniques - Khosro Zohrevandi; Hossein Ahmadi; Hamid Khalaji (Research in English Language Pedagogy, 2024)
Previous research indicates that task-based collaborative output activities (TBCOA) and scaffolding techniques (ST) lead to improvements in English as a foreign language (EFL) learners’ writing skill. However, there seems to be a lack of research on the comparative effects of these activities and techniques on EFL learners' writing accuracy and fluency. Therefore, the present study aimed to investigate the comparative impacts of two types of TBCOA (debating and dictogloss) versus two types of ST (teacher and peer scaffolding) on Iranian intermediate EFL learners' writing accuracy and fluency (A&F). This research followed a quasi-experimental design. A sample of 80 intermediate-level EFL learners, selected through convenience sampling from a Language School in Malayer, constituted the participants of the study. The learners were divided into four groups (each with 20 members). The homogeneity of the participants in terms of writing A&F was checked through a pretest at the outset of the study. Paired-sample t-tests were run to examine the possible significant changes in scores from the pretest to the posttest in each group. Furthermore, the effects of debating vs. dictogloss, teacher scaffolding vs. peer scaffolding, and overall TBCOA vs. overall ST were compared through ANCOVA, with the pretest scores being treated as the covariate. It was found that debating significantly led to more improvement than dictogloss in the learners' writing A&F. Moreover, teacher scaffolding was more effective than peer scaffolding. Regarding overall TBCOA and ST, the latter was significantly more effective. This research provides implications for EFL writing instruction.